Effects of a meal replacement system alone or in combination with phentermine on weight loss and food cravings. Issue 11 (24th September 2016) - Moldovan, Christina P.; Weldon, Abby J.; Daher, Noha S.; Schneider, Louise E.; Bellinger, Denise L.; Berk, Lee S.; Hermé, Alyson C.; Aréchiga, Adam L.; Davis, Willie L.; Peters, Warren R.
Abstract : Objective: To examine the effects of phentermine combined with a meal replacement program on weight loss and food cravings and to investigate the relationship between food cravings and weight loss. Methods: In a 12‐week randomized, double‐blind, placebo‐controlled clinical trial, 77 adults with obesity received either phentermine or placebo. All participants were provided Medifast ® meal replacements, were instructed to follow the Take Shape for Life ® Optimal Weight 5&1 Plan for weight loss, and received lifestyle coaching in the Habits of Health program. The Food Craving Inventory and the General Food Cravings State and Trait Questionnaires were used to measure food cravings. Results: The phentermine group lost 12.1% of baseline body weight compared with 8.8% in the placebo group. Cravings for all food groups decreased in both groups; however, there was a greater reduction in cravings for fats and sweets in the phentermine group compared with the placebo group. Percent weight loss correlated significantly with reduced total food cravings ( r = 0.332, P = 0.009), cravings for sweets ( r = 0.412, P < 0.000), and state food cravings ( r = 0.320, P = 0.007). Conclusions: Both phentermine combined with a meal replacement program and meal replacements alone significantly reduced body weight and food cravings; however, the addition of phentermine enhanced these effects.